1965
DOI: 10.1038/bjc.1965.32
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Tumour Growth: Comparison of Growth Rates and Extrapolation of Growth Curve to One Cell

Abstract: RECENTLY we have shown (Laird, 1964) that the growth of a variety of tumors of the mouse, rat and rabbit, whether transplanted or primary, is well described by a Gompertzian equation. Such growth may be regarded as an exponential process limited by an exponential retardation, and tumor growth was therefore interpreted as being due mainly, if not entirely, to an exponential proliferation of tumor cells whose successive mean generation times increase according to an exponential equation.For the present study, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
231
0
7

Year Published

1966
1966
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(246 citation statements)
references
References 7 publications
8
231
0
7
Order By: Relevance
“…This specific pattern is not observed in rats. Rather, skeletal growth of the rat proceeds continuously through the juvenile and prepubertal phases along an exponential trajectory evident at birth (Laird, 1965b;Kilborn et al, 2002), which later decays as a function of animal age and endocrine activity. In this study, we have observed that significant longitudinal growth enters a decay phase at approximately 64 days of age, lagging slightly behind the reported age at which sexual maturity is assumed by the appearance of mature spermatozoa in the vas deferens in male (45-55 days), or the first ovulation in female (35-40 days) rats (Ojeda and Urbanski, 1994).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This specific pattern is not observed in rats. Rather, skeletal growth of the rat proceeds continuously through the juvenile and prepubertal phases along an exponential trajectory evident at birth (Laird, 1965b;Kilborn et al, 2002), which later decays as a function of animal age and endocrine activity. In this study, we have observed that significant longitudinal growth enters a decay phase at approximately 64 days of age, lagging slightly behind the reported age at which sexual maturity is assumed by the appearance of mature spermatozoa in the vas deferens in male (45-55 days), or the first ovulation in female (35-40 days) rats (Ojeda and Urbanski, 1994).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The SCs at 12 and 18 months (SC12 and SC18) were obtained from the nonlinear logistic function used by Nelder (1961). This was found to be the best out of six nonlinear curves for SC growth that were tried out in relation to the present database: Brody, Richards, Von Bertalanffy, Logistic, Gompertz and modified Logistic form, respectively, Brody (1945), Richards (1959), Von Bertalanffy (1957), Nelder (1961), Laird (1965) and Quirino et al (1999). The nonlinear logistic function was described as follows:…”
Section: Methodsmentioning
confidence: 99%
“…However, it is known that the growth of cattle is described by a sigmoid curve. Thus, it is expected that nonlinear models would describe their body growth better (Laird, 1965). For beef cattle, in particular Zebu breeds, the standard ages of 205, 365 and 550 days are used.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these implies different model-specific dynamics of tumour g2rowth (Mendelsohn. 1963: Laird. 1965: Steel and Lamerton.…”
mentioning
confidence: 99%